2008
DOI: 10.1121/1.2935583
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of traffic noise

Abstract: When modeling a city or a secondary road to calculate a noise map, the information about the number of heavy/light vehicles and the average speed it is not always available. In this paper, a first approach to get an automatic classification of vehicles is presented. The system is based on the classification of the audio signal that a noise source produces. Some basic classifiers have been tested (k-nearest neighbours, FLD (Fischer linear discriminator) and principal components. As first approach, the aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Those statistic values are the final feature values that characterize the input audio signal. The features considered here are [8,9,10],…”
Section: Experimentation and Resultsmentioning
confidence: 99%
“…Those statistic values are the final feature values that characterize the input audio signal. The features considered here are [8,9,10],…”
Section: Experimentation and Resultsmentioning
confidence: 99%
“…The major challenge in this field is the automatic classification of audio [27]. Recent studies on the classification of traffic noise have been conducted, for example, to identify the type of vehicle through roadside noise [28,29] and evaluate passengers' subjective experience by categorizing the cabin's interior noise [30]. However, compared with traffic noise, the factors influencing vehicle interior noise of subway trains are considerably more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In combination with a Multilayer Neural Network, both MPEG-7 and MFCC attained the highest averaged recognition accuracies in a corpus containing road vehicles, aircrafts, trains and industrial noises. Besides comparing different signal features, Fisher Linear Discriminant and K-Nearest Neighbor (KNN) were evaluated in (Sobreira et al, 2008) for the recognition of specifically road traffic noise sources (cars, trucks and scooters). Experimental results showed that KNN was the machine learning technique yielding the best performance, specifically when considering feature combination (MFCC, Sub-band Energy Ratio (SBER) and Spectral Roll-Off (SRO)).…”
Section: Related Workmentioning
confidence: 99%